Identification of a regulatory function for an orphan receptor in muscle: COUP-TF II affects the expression of the myoD gene family during myogenesis. - Muscat, G E (1995)
COUP-TF II is an 'orphan steroid receptor' that binds a wide variety of AGGTCA repeats and represses thyroid hormone (T3) and retinoid dependent trans-activation; however, very little is known of its functional and/or developmental role during mammalian cell differentiation. T3 and retinoids have been demonstrated to promote terminal muscle differentiation via activation of the muscle specific myoD gene family (myoD, myogenin, myf-5 and MRF-4). The myoD gene family can direct the fate of mesodermal cell lineages, repress proliferation, activate differentiation and the contractile phenotype. Hence, we investigated the expression and functional role of COUP-TF II during muscle differentiation. Proliferating C2C12 myoblasts expressed COUP-TF II mRNA which was repressed when cells were induced to differentiate into post-mitotic multinucleated myotubes by serum withdrawal. Concomitant with the decrease of COUP-TF II mRNA was the appearance of muscle specific mRNAs (e.g. myogenin, alpha-actin). We show that Escherichia coli expressed full length and truncated COUP-TF II bound in a sequence specific manner to the T3 response elements (TREs) in the myoD and myogenin regulatory HLH genes [Olson (1992) Dev. Biol. 154, 261-272]; and the TRE in the skeletal alpha-actin contractile protein gene. COUP-TF II diminished the homodimeric binding of the thyroid hormone receptor and the heterodimeric binding of thyroid hormone and retinoid X receptor complexes to these TREs. Constitutive over-expression of COUP-TF II cDNA in mouse C2C12 myogenic cells suppressed the levels of myoD mRNA and blocked the induction of myogenin mRNA, whereas constitutive expression of anti-sense COUP-TF II cDNA significantly increased the steady state levels of myoD mRNA and hyper-induced myogenin mRNA. These studies demonstrate for the first time (i) that COUP-TF II, functions as a physiologically relevant antagonistic regulator of myogenesis via direct effects on the myoD gene family and (ii) direct evidence for the developmental role of COUP-TF II during mammalian cell differentiation.